Modeling User Preference Factors for Trans Koetaradja Feeder Bus and Battery Electric Vehicle Adoption - Meilinda, Iqra Mona; Afiqa Dhaifina; Aqlima Putri; Ucha Arief Pratama; Aulia Rahmad (Program Studi Sarjana Teknik Sipil Universitas Internasional Batam, 2025)
The Aceh Transportation Agency has introduced the Trans Koetaradja Feeder Bus as a public transportation facility for the community to reach residential areas or housing complexes. However, the Trans Koetaradja service still faces limitations in accessing settlements located in remote areas, making it difficult for residents to reach the available routes. To expand coverage to more evenly distributed residential areas, including remote regions, while simultaneously reducing passenger travel time to their destinations, the operation of Battery-Based Electric Motor Vehicles (KBLBB) is planned as a small-scale public transport mode. This study aims to identify the characteristics of travelers and the factors influencing preferences for using the Trans Koetaradja Feeder Bus and KBLBB through a Structural Equation Modeling (SEM) approach. Research data were obtained using the Stated Preference (SP) method by involving 200 respondents through questionnaire distribution. The questionnaires were distributed to Trans Koetaradja users and residents living around Feeder Route 7 (Masjid Raya Baiturrahman – Lambaro) via Lueng Bata. The results showed that accessibility was the most dominant factor influencing user preferences, reflecting public concerns about the considerable distance from homes to bus shelters/stops, which potentially causes delays in daily activities. Therefore, the community welcomed the presence of KBLBB as a solution. Furthermore, the SEM modeling results with Confirmatory Factor Analysis (CFA) produced a significant measurement model, in which the variable “accessibility” was proven to influence “comfort.” Indicators within the “accessibility” construct were identified as the main factors contributing to users’ perception of comfort.